KOLABORASI SEBAGAI STRATEGI PEMBELAJARAN MI : TINJAUAN LITERATUR TERHADAP MODEL JIGSAW, THINK PAIR SHARE (TPS), DAN GROUP INVESTIGATION (GI) - Widya Mufidatul ‘Ula; Eka Duwi Ardianti; Nadya Ayu Lifiani; Mu’minatut Thowafiah; Audy Putri Cahyani; Suttrisno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Collaborative and cooperative learning are currently widely applied in modern education to increase student participation and academic achievement. This study adopts a literature review method by collecting and analyzing various sources, such as books, research reports, journals, and articles related to both learning approaches. One of the problems discussed in this article is the imbalance in participation between students and teachers, where students tend to be passive during learning, reducing the effectiveness of the learning process. In addition, in the 21st century, students are required to master collaborative skills in solving problems, making the participatory approach increasingly important. Before implementing the learning process, educators need to prepare a thorough plan in the form of a teaching module or Learning Implementation Plan (RPP) that includes various components of strategies, methods, and learning models. The learning strategy itself is a combination of three fundamental aspects: theoretical foundations (science), pedagogical innovation (art), and practical competence (skills) applied by teachers in guiding students, providing motivation, and creating an optimal learning atmosphere. In the contemporary education system, collaborative and cooperative approaches have developed as significant learning methods. Both models emphasize social interaction and cooperation between students in order to optimize conceptual understanding. This learning process is designed so that students can master the subject matter through mutually supportive group activities. Collaborative/cooperative models not only strengthen students' social interactions but also train communication and teamwork skills. This kind of approach is very suitable for application at the elementary education level (MI/SD). Based on the results of the analysis, the collaborative approach has proven effective in honing students' high-level thinking skills through interactive dialogue, while the cooperative method shows advantages in achieving learning targets in a more structured manner.